The effectiveness of adding BTS teaching materials to improve the reading ability of Korean language students - Khairunnisa, Fakhirah; Herniwati, Herniwati; Triarisanti, Risa (Universitas Pendidikan Indonesia (UPI), 2022)
In the current era, knowledge and technology are rapidly advancing. The rapid development of technology makes it easier for people to access the world. This study aims to determine the effectiveness of Learn Korean with BTS teaching materials in improving Korean reading skills with a sample of 46 Korean Language Education students year of 2020. The data collection technique used test instruments and questionnaires totalling 20 valid and reliable items each. This study used a quasi-experimental research method and the non-equivalent control group design. The results showed that the experimental class got an average pre-test result of 60.87 and an average post-test result of 85.43, while the control class got an average pre-test result of 62.83 and an average post-test result of 68.04. The paired sample t-test was used to determine differences in learning outcomes and the test results showed the significance value (2-tailed) was 0.00 (0.05), which means that there is a significant difference in the results of students’ learning before and after using the Learn Korean with BTS teaching materials. The results of the independent sample t-test show a significance value (2-tailed) was 0.00 (0.05), which means that there is a significant difference in learning outcomes between students who used Learn Korean with BTS teaching materials and those who used traditional learning materials. The results of the questionnaire show that students' opinions about learning using the Learn Korean with BTS teaching materials are positive.